Utilization of research for elite sport in the Czech Republic - Nova, J. (SportMont, 2017)
In 2015 and 2016, the author conducted an audit of the Czech national elite sports policy using the international research methodology called SPLISS (Sports Policy Factors Leading to International Sporting Success). Based on the audit results in Pillar 9 this paper analyses the situation regarding the existence of structural factors for the dissemination of research applicable in elite sport and the extent to which these research outputs serve as scientific input to elite sport in the Czech Republic. The results from this qualitative and quantitative study focus on the utilization of knowledge from sport science in a country context, providing the base for a comparison with other countries and proposing the way towards effective and efficient cooperation between academia and sport practice in this regard.